STRATEGI KOMUNIKASI DALAM MENGEMBANGKAN RETORIKA DAKWAH MAHASANTRI DALAM KEGIATAN MUHADHARAH DI MA’HAD AL-JAMIAH UNIVERITAS ISLAM NEGERI RADEN INTAN LAMPUNG (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the importance of the quality of the rhetoric of Islamic preaching of students in muhadharah activities at Ma'had Al-Jami'ah UIN Raden Intan Lampung. Although the digitalization era is increasingly developing, muhadharah remains a relevant forum among students to be used as a means of practice in developing public speaking and Islamic preaching skills, however, many students still experience limitations in conveying messages effectively, such as unstructured delivery, weak persuasion techniques, reliance on texts, and lack of interaction with the audience. This problem shows that rhetorical skills are not sufficiently developed through practice alone, but require systematic and planned communication strategies. Therefore, this study aims to analyze the communication strategies applied by students in developing Islamic preaching rhetoric through muhadharah activities. This study uses a qualitative approach with the type of field research, through observation techniques, in-depth interviews, and documentation. Data analysis uses the Miles and Huberman model which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that effective communication strategies such as audience analysis, structured message planning, appropriate language use, persuasive rhetorical techniques, and ongoing evaluation play a significant role in improving the rhetorical competence of students. Muhadarah activities have a significant impact and contribute significantly to honing students' speaking skills, while strengthening religious and social values ​​that are beneficial in everyday life. This study recommends strengthening the muhadarah program as part of the development of da'wah rhetoric at Ma'had Al-Jamiah UIN Raden Intan Lampung.